Effects and Safety of Oral Iron for Heart Failure with Iron Deficiency: A Systematic Review and Meta-Analysis with Trial Sequential Analysis - Nannan Tan; Yiqing Cai; Junjie Liu; Xiaoping Wang; Lin Ma; Guanjing Ling; Jinchi Jiang; Qiyan Wang; Yong Wang (Cardiovascular Therapeutics)
Background. Oral iron supplement is commonly prescribed to heart failure patients with iron deficiency. However, the effects of oral iron for heart failure remain controversial. This study included randomized controlled trials (RCTs) for meta-analysis to evaluate the effects of oral iron for heart failure patients. Methods. Nine databases (The Cochrane Library, Embase, PubMed, CINAHL, Web of science, CNKI, SinoMed, VIP, and Wanfang) were searched for RCTs of oral iron for heart failure from inception to October 2021. The effects were assessed with a meta-analysis using Revman 5.3 software. The trial sequential analysis was performed by TSA 0.9.5.10 beta software. The risk of bias of trials was evaluated via Risk of Bias tool. The evidence quality was assessed through GRADE tool. Results. Four studies including 582 patients with heart failure and iron deficiency were enrolled. The results indicated that oral iron treatment could improve left ventricular ejection fraction (LVEF, MD=1.52%, 95% CI: 0.69 to 2.36, P=0.0003) and serum ferritin (MD=1.64, 95% CI: 0.26 to 3.02, P=0.02). However, there was no between-group difference in the 6-minute walk distances (6MWT), N terminal pro B type natriuretic peptide (NT-proBNP) or hemoglobin level when compared with control group. Subgroup analyses revealed that the effects of oral iron on 6 MWT and serum ferritin could not be affected by duration and frequency of oral iron uptakes. In trial sequential analysis of LVEF and serum ferritin, the Z-curves crossed the traditional boundary and trail sequential monitoring boundary but did not reach the required information size. Conclusion. This analysis showed that oral iron could improve cardiac function measured by LVEF, and iron stores measured serum ferritin, but lack of effect on exercise capacity measured by 6 MWT, and iron stores measured by hemoglobin. Given the overall poor methodological quality and evidence quality, these findings should be treated cautiously.